WRITING-INTENSIVE COURSES ACROSS THE LAW CURRICULUM: DEVELOPING LAW STUDENTS’ CRITICAL THINKING AND WRITING SKILLS – A POST-EVALUATION ASSESSMENT - Theo Broodryk; Melandie Buitendag (Obiter, 2015)
This article follows upon a previous article which dealt with the writing-across-the curriculum strategy implemented at the Faculty of Law, Stellenbosch University. This article details the findings and recommendations of an outcomes evaluation conducted in respect of the strategy, commissioned by the Faculty, and deals with the design, implementation and achievement of outcomes by the strategy. It commences by considering the different components of the strategy, the implementation of these components and the relevant findings of the outcomes evaluation in this regard. Specific attention is given to the five mainstream outcomes envisaged by the Faculty through the implementation of the strategy’s different but mutually complementary components. The article will conclude by making recommendations aimed at ensuring the continuous development and improvement of the strategy, not only at the Faculty, but also in an attempt to assist other law faculties in the implementation or improvement of their own writing initiatives.